The CSI project delivery practice guide - Construction Specifications Institute (New Jersey : John Wiley & Sons, 2011)
Get the must-have reference on standards and best practices for the delivery of a construction project. The CSI Practice Guides are a library of comprehensive references specifically and carefully designed for the construction professional. Each book examines important concepts and best practices integral to a particular aspect of the construction process. Laying the foundation for this series, The CSI Project Delivery Practice Guide provides fundamental knowledge for the documentation, administration, and successful delivery of construction projects. It also serves as the pivotal starting point for understanding CSI's core values, as well as a useful study aid for those wishing to obtain the Construction Documents Technologist certificate.
The CSI Project Delivery Practice Guide; Contents; Preface; Acknowledgments; Chapter 1 Introduction to The CSI Project Delivery Practice Guide; 1.1 Introduction; 1.2 Understanding Project Delivery as Foundational Knowledge; 1.3 Magnitude of Design and Construction Information Available; 1.4 Managing Information; 1.5 The Nature of the Project and Facility; Chapter 2 Stakeholders and Participants; 2.1 Introduction; 2.2 The Owner Team; 2.3 The Design Team; 2.4 The Contractor Team; 2.5 The Supplier Team; 2.6 Team Selection Process; 2.7 Partnering and Collaboration; 2.8 Commissioning.
Includes index.
Keywords: Construction projects -- Management; Construction industry -- Management